State-of-Art on Self-Lubricating Ceramics and Application of Cu/CuO as Solid Lubricant Material. Issue 1 (2nd January 2023) - Singh, Bipin Kumar
Abstract : The intention of this paper is to make a comprehensive discussion on self-lubricating ceramics along with the application of Cu/CuO as a solid lubricant. So, the article starts with a discussion on all the problems associated with conventional solid lubricants and its continual modifications. Furthermore, a new era of solid lubricants, its benefits and why they are recommended ov er conventional lubricants are thoroughly discussed. After this, the discussion starts with the fundamental mechanism along with the underlying physics of the self-lubricating phenomenon and is rev iewed. Later, the discussion highlights the processing method and application of Cu/CuO as a solid lubricant with its experimental results. The discussion also encompasses the effect of testing conditions, counterpart and environmental conditions on the functional properties. Finally, the practical and possible future applications of Cu/CuO as solid-lubricant are discussed. GRAPHICAL ABSTRACT: UF0001